Pengembangan Mi Lethek Sebagai Kuliner Unggulan Bantul - Noviani, Wulan; Ramadhan, Cahyo Setiadi; Suprabowo, Imam (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2019)
Mi LethekÂ  (Lethek Noodle) is made from Bantul original cassava. Its selling creation and packaging are potentially developed. The objective to develop Mi Lethek noodle is to increase the added value and selling value of Bantulâ€™s superior culinary product. The method used was providing training and coaching on the selling tips and creative packaging, monitoring and evaluation towards the producers and the management. The results obtained are the producer label establishment of Mi Lethek Asli Bendo with Garuda brand, the noodle product with new packaging, and online marketing media.